Retour sur les dix-sept premières années du Prix Mnémosyne - Jean-Baptiste Bonnard; Camille Noûs (Genre & Histoire)
This article traces the history and the operation of the Prix Mnémosyne since it was founded in 2003. It examines the distribution, by historic periods, of the prize-winning Master’s dissertations as well as the composition of the jury. The over-representation of the contemporary period not only in the number of essays in competition but also in the composition of the jury and the publication of books based on the winning dissertations reflect the importance of this period in the field of historical studies. The major role played by a small number of institutions where many of these essays were produced (Bordeaux-Montaigne, Caen, Lyon II, Paris VII, Rennes, Strasbourg and particularly the EHESS, Toulouse, Paris I and Paris IV) bears witness to the vitality of studies into the history of women and gender in part of the French university landscape.